Effect of hydrogeomorphic setting on calcareous fen hydrology. Issue 11 (15th May 2018) - Duval, Tim P.; Waddington, James Michael
Abstract: Calcareous fens are species‐rich peatlands that are dependent on minerotrophic water sources for wetland functioning, with current conceptual models suggesting the water source is ubiquitously groundwater upwelling. By quantifying the water balance and subsurface water flow paths and fluxes over 3 growing seasons for calcareous fens in 3 different hydrogeomorphic settings (Riparian, Trough, and Basin), we show evidence that challenges this conceptual model. The Riparian Fen received an order of magnitude more water inputs than the Trough or Basin Fens and was dominated by stream recharge inputs and groundwater outputs. Precipitation and evaporation dominated the water balance of the Trough Fen whereas only the Basin Fen received sizeable groundwater inputs. Indeed, subsurface water fluxes were low at all fens due to weak hydraulic gradients and low saturated hydraulic conductivity in some areas of each wetland, though variations in growing season precipitation led to subsurface flow reversals in all 3 fens. Our results demonstrate the importance of understanding landscape position, or hydrogeomorphic setting, on calcareous fen hydrology for improving conservation, management, and restoration efforts of these important ecosystems.